Uterine leiomyomata: a retrospective study of correlations with hypertension and diabetes mellitus from the Japan Nurses' Health Study. (17th November 2018) - Yasui, Toshiyuki; Hayashi, Kunihiko; Okano, Hiroya; Kamio, Masayo; Mizunuma, Hideki; Kubota, Toshiro; Lee, Jung-Su; Suzuki, Shosuke
Abstract: We performed a scrutiny survey of self-reported uterine leiomyomata (UL) to investigate the associations of parental history with hypertension and personal history of hypertension in the UL cases in Japanese women. Questionnaires that included items on the sites of UL determined by imaging techniques and surgical procedure were mailed to 2015 women with a self-reported UL at a baseline survey of the Japan Nurses' Health Study ( n  = 15, 019). We found that women with a past history and a maternal history of hypertension had an increase in their risk of UL. A maternal history of hypertension was significantly associated with an increase in the risk of UL in women without a past history of hypertension but not in the women with a past history of hypertension. A past history and a parental history of diabetes mellitus were not associated with an increase in the risk of UL. Women of reproductive age with a maternal history of hypertension may be at a higher risk for hypertension and UL. Impact Statement: What is already known on this subject? A positive association of uterine leiomyomata (UL) with a past history of hypertension has been found but the association of a parental history of hypertension with UL has not yet been clarified. What do the results of this study add? Maternal hypertension, as well as a personal history of hypertension, was associated with an increased risk of UL and a past history and a parental history of diabetes mellitus were not associated with an increase in the risk of UL. What are the implications of these findings for clinical practice and/or further research? Women of a reproductive age with a maternal history of hypertension may be at a higher risk for hypertension and UL.